The acceptance and use of a virtual learning environment in higher education: an empirical study in Turkey, and the UK - Özlem Efiloglu Kurt (International Journal of Educational Technology in Higher Education, 2017)
This study evaluated the acceptance and use of a virtual learning environment in higher education by using the unifi ed theory of acceptance and use of technology (UTAUT) model. Study data were collected by means of a questionnaire form, completed by 1032 students receiving undergraduate educat ion in Turkey and the United Kingdom, who currently use similar virtual learning environments. The role of performance expectancy, effort expectancy, social influence and facilitating conditions were evaluated and tested for both countries. The study results demons trated that the behavioral intention and use behavior regarding the utilization of a virtual learning environment in higher education differed between the two countries, and that t he level of impact of the factors that shape behavioral intention and use behavior also differed from one factor to another.